Retrospective analysis of statistical indicators for vegetable and animal agricultural products optained in the conventional system and in ecological agriculture - Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The aim pursued in the paper is the analysis of the transformations that took place, in the period 2007-2019, at the level of the two conventional and ecological production systems. The analysis of the statistical data series, INS Tempo-ONLINE and EUROSTAT data for conventional and organic agriculture, was used to reflect the level and trends of economic statistics in agriculture. The need to characterize the evolution and structure of agricultural phenomena also determined the calculation of statistical indicators (average, standard deviation, coefficient of variability, annual growth rate, etc.) from the perspective of cultivated areas, total yields, production yield per hectare and on the head of an animal, etc. This method responds to a well-defined goal: the data series through the calculated indicators highlight the upward / downward trend and help to determine the indicative socio-economic development of the regions taking into account the differentiated growth rates of the systems in each region. The study provides and contributes to information, by knowing the evolution over time of plant and animal agricultural products, obtained conventionally and in organic farming.
Keywords: D20; O5; Q01; Q13; Q17; 330; agricultural products; statistical indicators; conventional system; ecological agriculture